Nascent Myth - Krueger, September E. (East Carolina University, 2010)
This is a written report of a creative thesis. The body of work presented in "Nascent  Myth" evolved from personal exploration regarding myth and spirituality. Birds are used as the unifying element to present several aspects of mythology. I address mythology as our connection to the mysterious, and I will share my spiritual experiences partnered with the myths. A  contemporary context is used to address the social implications that challenge our perception of  myth.
Keywords: Fine arts; Serigraphy, American; Quilts in art; Textile fabrics in art; Myth in art; Spirituality in art; Birds in art